STRATEGI KOMUNIKASI UNIVERSITAS MUHAMMADIYAH JAKARTA DALAM MEMBANGUN BRAND IMAGE MELALUI PEMERINGKATAN UNIRANK - Budiman; Nani Nurani Muksin (SOSFILKOM : Jurnal Sosial, Filsafat dan Komunikasi, 2025)
This study aims to describe the communication strategy of Universitas Muhammadiyah Jakarta (UMJ) in building its brand image through the UniRank 4ICU ranking indicators. As the oldest Muhammadiyah higher education institution, established in 1955, UMJ holds a strategic position in Indonesia’s higher education landscape. Therefore, UMJ bears the responsibility to project an image of excellence, uniqueness, and strong institutional reputation, particularly in the digital era. This research employs a descriptive qualitative approach, guided by Cangara’s theory of communication strategy and Keller’s Customer-Based Brand Equity (CBBE) model. Data collection was conducted through in-depth interviews, and thematic analysis was carried out based on the CBBE framework and UniRank indicators, including referring domains, global rank, domain authority, and trust flow. The findings indicate that UMJ strategically implements these ranking indicators through the management of its official website, social media platforms, and the application of search engine optimization (SEO) techniques. These efforts form part of the university’s broader communication strategy to build a strong institutional brand image. The achievement of a global ranking not only reflects digital communication performance but also serves as a strategic communication tool that reinforces UMJ’s image as a modern, reputable, and Islamic-oriented higher education institution. This study underscores the importance of integrating digital communication strategies with brand image development to enhance institutional competitiveness at the global level.